A statistical analysis on Non Soap Detergent Company - Abarquez, Joselito; Esguerra, Kathryn L.; Inumerable, Jennifer V. (Diliman, Quezon City College of Engineering, 2002)
"Quality is the totality of features and characteristics of a product or service that bear on its ability to satisfy stated or implied needs," according to the American Society of Quality Control. A statistical analysis was conducted on NSD Company, which manufactures consumer products such as bath soaps, detergent bars, shampoos, and toothpastes. The study included documentation and analyses of the present production system of Laundry bars, and statistical analyses on the factors affecting its weight, which was determined to be the core problem of the production system.Using a Pareto chart, the group was able to determine the core problem of the company, incorrect bar weights. The streamline diagnosis diagram was then used to identify the root causes of the problem identified through the Pareto such as plodder speed, vacuum pressure and work shift. The Ishikawa diagram was also used to directly focus the causes of the problem. A goodness of fit test was utilized to prove that the raw data obtained satisfy the normality assumption. The 2 factorial design was then performed to determine if the factors have a significant effect on the problem. Then, a regression model of the experiment results was established using regression analysis. A normal probability plot was also drawn to further show the significance of the interaction between factors. Residual plotting, on the other hand, was done to show the variability within levels of factors. From the results of the statistical tools mentioned above, it was concluded that plodder vacuum pressure, work shifts, plodder speed and their interactions significantly cause variations in the net weight of Laundry bar. With these findings, it is recommended that the company maintain low vacuum pressure and regular plodding speed to minimize variations in bar weight. Furthermore, the 1st shift, which is used for start-ups and adjustments, can be monitored more carefully at the start of production to minimize its undesirable effects. An automatic monitoring system being used by the company in their new plodder line can also be applied to the existing lines, though this can be costly.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering